1974
DOI: 10.1097/00004032-197409000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Distribution and Milk Secretion of Radionuclides by the Dairy Cow III. Radiotellurium

Abstract: Four lactating cows were confined in metabolism stalls and each given a single oral dose ~f~~~~T e .For the next 5 days, all milk, urine and feces from the cows were collected and the 129mTe content measured. The highest concentration of lmrnTe in the milk was 0.0035%/1.18 hr following administration of the nuclide. The activity decreasedwith a biological half-time in the milk of 38 hr. The total activity transferred to milk was limited with 0.254% of the administered nuclide secreted in approximately 13 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The half-life of 132 Te is 3.2 days and its decay product is radioactive 132 I, which is thyroid tropic. A previous study reported that radioactive tellurium that is orally administered to cows concentrates in the thyroid more than in most other tissues [19]. These results suggest that we need to pay more attention to 132 Te as well as 131 I in assessing health risk to the thyroid.…”
Section: Resultsmentioning
confidence: 89%
“…The half-life of 132 Te is 3.2 days and its decay product is radioactive 132 I, which is thyroid tropic. A previous study reported that radioactive tellurium that is orally administered to cows concentrates in the thyroid more than in most other tissues [19]. These results suggest that we need to pay more attention to 132 Te as well as 131 I in assessing health risk to the thyroid.…”
Section: Resultsmentioning
confidence: 89%
“…In a review by Hamilton (1948), the f 1 for tellurium was reported to be about 0.25 in rats. Mullen and Stanly (1974) reported that 0.25 of tellurate fraction was absorbed from the alimentary tract of dairy cows. The ICRP (1979) adopted an f 1 value of 0.2 for acute intakes by workers and 0.3 for chronic intakes by the general public (ICRP 1993 and 1996).…”
Section: Literature Reviewmentioning
confidence: 99%